Preaching Romans : Proclaiming God's Saving Grace - Matera, Frank J. (Book collections on Project MUSE., 2010)
"Although Paul's letter to the Romans is the most theologically charged writing of the New Testament, it is rarely preached from Catholic pulpits. Perhaps some of the Pauline themes---redemption and sanctification, justification and reconciliation, resurrection and parousia---seem too daunting for homiletic purposes. Not so, insists Frank Matera, who has learned to preach in a "Pauline key" that has invigorated the whole of his preaching. Homilists who heretofore have avoided Romans will appreciate Matera's insights on this text that open innovative and important ways of proclaiming the gospel. This slender volume is a gift to homilists who wish to preach from Romans with greater confidence---and to proclaim Paul's theologically rich and assuring message of God's saving grace." ""Homilists who have avoided preaching Paul's powerful but daunting Letter to the Romans needn't shirk their duty any longer. Matera's book does it all---biblical exposition, sample homilies with post-delivery analysis, and explicit strategies for preparing homilies. This is a rare and valuable pastoral resource written by one of the best contemporary Catholic interpreters of Paul. A m̀ust have' reference for preachers! Also valuable for anyone wanting to know more about Romans and its message for today."--Jacket.